1989
DOI: 10.1200/jco.1989.7.11.1685
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor stimulates recovery of granulocytes in patients receiving dose-intensive chemotherapy without bone marrow transplantation.

Abstract: Bone marrow colony-stimulating factors (CSF) ameliorate hematologic toxicity of standard chemotherapy regimens and may allow relatively safe use of intensive and more efficacious doses of anticancer drugs. Twenty-four patients with cancers for which no standard regimens were likely to be effective received repeated courses of a combination of cisplatin (150 mg/m2), etoposide (1,500 mg/m2), and cyclophosphamide (5,000 mg/m2) at doses for which bone marrow transplantation is usually used. A total of 10 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…20,21 Soon after cloning of G-CSF its clinical potential was realized to counteract chemotherapy-induced neutropenia. [22][23][24] Today, G-CSF has been given to over three million patients worldwide for this and related indications such as bone-marrow harvesting, idiopathic neutropenias, and appears as a well-tolerated drug.…”
Section: Background: Known Characteristics Of G-csfmentioning
confidence: 99%
“…20,21 Soon after cloning of G-CSF its clinical potential was realized to counteract chemotherapy-induced neutropenia. [22][23][24] Today, G-CSF has been given to over three million patients worldwide for this and related indications such as bone-marrow harvesting, idiopathic neutropenias, and appears as a well-tolerated drug.…”
Section: Background: Known Characteristics Of G-csfmentioning
confidence: 99%
“…Although G-CSF has been used in many patients to counter the side effects of chemotherapy as well as to prepare donors for peripheral cell harvesting, some concerns regarding its long-term safety still remain. [2][3][4] G-CSF may have several beneficial effects in animals with stroke. 5,6 Thus, it was reported that rats treated with G-CSF following middle cerebral artery occlusion (MCAO) have smaller infarcts and better functional outcome compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…15,23,29 Atualmente ele é utilizado para tratar neutropenia induzida por agentes quimioterápicos, ou no transplante de medula óssea. [23][24][25][30][31][32][33] O G-CSF é uma droga liberada pelo FDA e pelo Ministério da Saúde no Brasil, tendo já sido administrada a milhões de pacientes em todo o mundo, e é bem tolerada pelo organismo humano. Mais recentemente, tem sido demonstrada uma surpreendente atividade do G-CSF no SNC, 13,17,20,22,[34][35][36][37][38] fato que adiciona um potencial regenerativo em várias doenças neurológicas.…”
Section: Terapia Celular E O G-csfunclassified